2013
DOI: 10.4097/kjae.2013.65.5.431
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopic analysis of lumbar epidural contrast spread after retrograde interlaminar ventral epidural injection (RIVEI)

Abstract: BackgroundRetrograde interlaminar ventral epidural injection (RIVEI) may hypothetically be more effective if the catheter is placed at the ventrocaudal aspect of the exiting nerve. We tested that hypothesis by measuring ventral and dorsal epidural contrast flow during RIVEI.MethodsTo perform RIVEI, a 17 G Tuohy needle was inserted to access the epidural space. A 19 G epidural catheter was inserted and advanced through the needle, passing in a caudal direction to the lower aspect of the contralateral pedicle. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Previous studies suggested that the use of a retrograde interlaminar dorsal epidural approach with ventral epidural catheterization may be an effective approach to deliver medication to the target site [14,15,20]. Although the catheter is placed in the dorsal epidural space, contrast medium is delivered evenly to both the ventral and dorsal epidural spaces [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that the use of a retrograde interlaminar dorsal epidural approach with ventral epidural catheterization may be an effective approach to deliver medication to the target site [14,15,20]. Although the catheter is placed in the dorsal epidural space, contrast medium is delivered evenly to both the ventral and dorsal epidural spaces [14].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that, in comparison with conventional TFESI, drugs can be delivered more effectively to the target site by retrograde interlaminar ventral epidural injection, usually at the ventral aspect of the nerve root sleeve, dorsal aspect of disc herniation, or stenotic lesion [14,20]. Moreover, in cases of dorsal epidural spread, the retrograde interlaminar approach showed greater flow than in the conventional transforaminal approach [14,20].…”
Section: Discussionmentioning
confidence: 99%
“…The transforaminal approach (Fig. ) delivers medication around the affected nerve root with spread into the anterior epidural space . The caudal approach utilizes the opening at the sacral hiatus to deliver medication to the lower lumbar spine area .…”
Section: Interventional Options For Diagnosis and Treatment Of Low Bamentioning
confidence: 99%
“…An interlaminar epidural injection spreads into the dorsal epidural space and diffuses to the ventral target site [ 6 , 10 ]. Consequently, the concentration of the injecting agent is inadequate [ 11 ] or an epidural catheter should be inserted and positioned in the ventral epidural space [ 12 ]. TFEI can deliver the injectate precisely to the damaged nerve root and anterior epidural space, resulting in better outcomes, such as long-term efficacy and improved effects [ 1 , 6 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%